Harnessing small RNAs as synthetic post-transcriptional regulators in bacteria - Georg, Jens; Berghoff, Bork Ansgar; Schindler, Daniel (ACS synthetic biology, 2025)
Bacteria can respond to environmental changes by expressing small RNAs (sRNAs), which regulate mRNAs by complementary base-pairing. This regulatory mechanism allows bacteria to rapidly adapt their proteome. In recent years, sRNAs have gained attention as blueprints for synthetic regulators allowing control over user-defined targets. Multiple aspects need to be considered for efficient application of these versatile, on-demand, and easy-to-use tools. Advances in computational prediction and bioengineering concepts are the dawn of systematic synthetic sRNA biology. We provide an overview of sRNAs and alternative